Endurance athletes' stroke volume response to progressive exercise: A critical review - Rowland, T. (Sports Medicine, 2009)
Untrained subjects typically demonstrate a plateau in stroke volume beyond the early stages of an acute bout of progressive exercise. Some studies have indicated that the stroke volume pattern in highly trained endurance athletes may differ, continuing to rise progressively to the point of maximal exercise. This suggests that the mechanism for generating cardiac output in these athletes may be influenced by cardiac functional factors, particularly augmented diastolic filling. This review of studies assessing stroke volume changes with exercise in athletes reveals a wide disparity of reported patterns, ranging from those indicating a decline, to stable values (a true plateau), to a progressive increase to exhaustion of over 40%. Differences in testing methodology might help to explain these variable results, but which pattern truly reflects that expected in highly trained endurance athletes remains uncertain. Ancillary data suggest that if a non-plateau of stroke volume is typical of athletes, augmented diastolic filling might be the responsible mechanism. However, it is not clear whether this might reflect superior upstream (atrial pressure/volume) or downstream (ventricular diastolic function, compliance) factors.